Perinatal exposure to high dietary advanced glycation end products in transgenic NOD8.3 mice leads to pancreatic beta cell dysfunction. Issue 1 (2nd January 2018) - Borg, Danielle J.; Yap, Felicia Y. T.; Keshvari, Sahar; Simmons, David G.; Gallo, Linda A.; Fotheringham, Amelia K.; Zhuang, Aowen; Slattery, Robyn M.; Hasnain, Sumaira Z.; Coughlan, Melinda T.; Kantharidis, Phillip; Forbes, Josephine M.
ABSTRACT: The contribution of environmental factors to pancreatic islet damage in type 1 diabetes remains poorly understood. In this study, we crossed mice susceptible to type 1 diabetes, where parental male (CD8 + T cells specific for IGRP206-214 ; NOD8.3) and female (NOD/ShiLt) mice were randomized to a diet either low or high in AGE content and maintained on this diet throughout pregnancy and lactation. After weaning, NOD8.3 + female offspring were identified and maintained on the same parental feeding regimen for until day 28 of life. A low AGE diet, from conception to early postnatal life, decreased circulating AGE concentrations in the female offspring when compared to a high AGE diet. Insulin, proinsulin and glucagon secretion were greater in islets isolated from offspring in the low AGE diet group, which was akin to age matched non-diabetic C57BL/6 mice. Pancreatic islet expression of Ins2 gene was also higher in offspring from the low AGE diet group. Islet expression of glucagon, AGEs and the AGE receptor RAGE, were each reduced in low AGE fed offspring. Islet immune cell infiltration was also decreased in offspring exposed to a low AGE diet. Within pancreatic lymph nodes and spleen, the proportions of CD4 + and CD8 + T cells did not differ between groups. There were no significant changes in body weight, fasting glucose or glycemic hormones. This study demonstrates that reducing exposure to dietary AGEs throughout gestation, lactation and early postnatal life may benefit pancreatic islet secretion and immune infiltration in the type 1 diabetic susceptible mouse strain, NOD8.3.